Quantitative detection method for crystallization rate of casting powder and application

By melting, insulating and cooling the protective slag, image analysis is solved in the prior art, the problem of difficulty in detecting the crystallization rate of the protective slag and the results are affected by conditions, and accurate quantity detection of the crystallization rate of the protective slag is achieved, providing a theory Based on and guidance.

CN119395077APending Publication Date: 2025-02-07HUNAN VALIN XIANGTAN IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411610568.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the quantitative detection method for the crystallization rate of the protective slag requires sampling, which is difficult and has a high risk factor, and the detection results are affected by the continuous casting conditions of steel, so the crystallization strength of the protective slag itself cannot be accurately reflected.

Method used

The crystallization rate is obtained by melting, insulating and cooling the protective slag and performing image analysis. The insulation temperature is 1300℃~1400℃, and the insulation time is more than 30 minutes. This method is simple and easy to operate and can quantitatively detect the crystallization rate of the protective slag under the same conditions.

Benefits of technology

The accurate quantity detection of the crystallization rate of the protective slag is realized, which can reflect the crystallinity strength of the protective slag without being affected by external conditions, and provides theoretical basis and guidance for the application and composition optimization of continuous cast protective slag.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119395077A_ABST
    Figure CN119395077A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of steel smelting, and particularly relates to a quantitative detection method for the crystallization rate of casting powder and application. The quantitative detection method comprises the following steps: melting the casting powder, carrying out heat preservation, cooling, and carrying out image analysis to obtain the crystallization rate of the casting powder; the heat preservation temperature ranges from 1300 DEG C to 1400 DEG C, and the heat preservation time is 30 min or above. According to the quantitative detection method for the crystallization rate of the casting powder, the steps are simple, operation is easy, the crystallization rate of the casting powder is quantitatively detected under the same condition before the casting powder is put into use, then the crystallization capacity strength of different casting powder is compared, and theoretical basis and guidance are provided for application and component optimization of the continuous casting powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of steel smelting, and specifically relates to a method and application for quantitatively detecting the crystallization rate of protective slag. Background Art

[0002] In the continuous casting process of steel smelting, mold slag is used to lubricate the ingot and control the heat transfer rate. The heat transfer control function is directly related to the crystallization performance of the mold slag, and the crystallization temperature and crystallization rate are key indicators that reflect the strength of the crystallization performance of the mold slag. The crystallization temperature can be quantitatively obtained by a variety of methods; and for the crystallization rate of the mold slag, the crystallization strength of different mold slags is different, and the degree of crystallization needs to be reflected by comparing the crystallization rate. Therefore, it is necessary to quantitatively detect the crystallization rate of the mold slag, so as to analyze the degree of crystallization of the mold slag.

[0003] At present, the method for quantitatively detecting the crystallization rate of protective slag is to take out the solid slag film located in the middle position below the meniscus of the crystallizer wall from the site, and obtain the crystallization rate of the protective slag after inlaying (such as: fixing the sample in the mold and adding resin for inlaying), grinding and polishing (such as: grinding and polishing the inlaid sample until no obvious scratches can be seen under an optical microscope), and image analysis (crystallization performance analysis by image method), so as to determine the crystallization strength of the protective slag. However, this method not only requires sampling during the on-site production process, which is difficult and has a high risk factor; moreover, the crystallization rate of the protective slag obtained by sampling is affected by the current conditions of steel continuous casting (such as composition, temperature, etc.), and the crystallization rate obtained by detection cannot reflect the crystallization strength of the protective slag itself. Summary of the invention

[0004] The present application proposes a method and application for quantitatively detecting the crystallization rate of protective slag to solve at least one aspect of the above-mentioned technical problems.

[0005] This application is implemented through the following technical solutions:

[0006] In a first aspect, the present application provides a method for quantitatively detecting the crystallization rate of mold slag, comprising the following steps:

[0007] After the mold slag is melted, kept warm and cooled, image analysis is performed to obtain the crystallization rate of the mold slag;

[0008] The insulation temperature is 1300° C. to 1400° C., and the insulation time is more than 30 minutes.

[0009] In some possible implementations, the basicity of the protective slag is 0.5-2.0.

[0010] In some possible implementations, the protective slag is a carbon-free protective slag.

[0011] In some possible implementations, the insulation time is 30 min to 60 min.

[0012] In some possible implementations, the crystallization step includes: cooling the mold slag after heat preservation to 23° C. to 28° C. at a cooling rate of 20° C. / s to 50° C. / s to obtain a crystal sample.

[0013] In some possible implementations, the image analysis step includes:

[0014] Obtaining samples for analysis;

[0015] Obtaining a longitudinal cross-sectional photograph of the analysis sample;

[0016] The crystallization rate of the analyzed sample is identified and obtained using image analysis software.

[0017] In some possible implementations, the size of the analysis sample is 10 mm to 100 mm × 8 mm to 12 mm × 10 mm to 100 mm, except for 10 mm × 8 mm to 12 mm × 10 mm.

[0018] In some possible implementations, the image analysis software is Adobe Photoshop or ImageJ.

[0019] In some possible implementations, when the Adobe Photoshop is used to analyze a sample photo, the RGB values ​​of the crystallized portion in the photo are: R value 60-190, G value 50-200, and B value 45-195.

[0020] In some possible implementations, when the ImageJ is used to analyze a sample photo, the RGB values ​​of the crystallized part in the photo are: R value is 60-190, G value is 50-200, and B value is 45-195.

[0021] In a second aspect, the present application provides an application of the method for quantitatively detecting the crystallization rate of protective slag provided in the present application in the field of steel smelting technology.

[0022] The present invention provides a method for quantitatively detecting the crystallization rate of mold slag, which has at least the following beneficial technical effects compared with the prior art:

[0023] (1) The present application provides a quantitative detection method for the crystallization rate of the protective slag, wherein the protective slag is melted and then kept warm so that each component in the protective slag is completely and evenly melted.

[0024] (2) The method for quantitatively detecting the crystallization rate of the protective slag provided in the present application has simple steps and is easy to operate. Before the protective slag is put into use, the crystallization rate of the protective slag is quantitatively detected under the same conditions, and then the crystallization ability of different protective slags is compared, thereby providing a theoretical basis and guidance for the application and composition optimization of continuous casting protective slag. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present drawings or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present drawings. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0026] Figure 1 This is a morphology diagram of a sample analyzed in a method for quantitatively detecting the crystallization rate of mold slag in Example 1 of the present application;

[0027] Figure 2 This is a morphology diagram of a sample analyzed in a method for quantitatively detecting the crystallization rate of protective slag in Example 2 of the present application;

[0028] Figure 3 This is a morphology diagram of a sample analyzed in a method for quantitatively detecting the crystallization rate of mold slag in Example 3 of the present application;

[0029] Figure 4 This is a morphology diagram of a sample analyzed in a method for quantitatively detecting the crystallization rate of protective slag in Comparative Example 1 of the present application;

[0030] Figure 5 This is a morphology diagram of a sample analyzed in a method for quantitatively detecting the crystallization rate of protective slag in Comparative Example 2 of the present application;

[0031] Figure 6 This is an analysis diagram of the image analysis of the morphology of the analyzed sample in Example 2 of the present application.

[0032] The purpose, features and advantages of this figure will be further described in conjunction with the embodiments with reference to the accompanying drawings. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is described and illustrated below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. Based on the embodiments provided in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.

[0034] Obviously, the following descriptions are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios without creative work. In addition, it can also be understood that although the efforts made in this development process may be complicated and lengthy, for ordinary technicians in this field related to the content disclosed in this application, some changes in design, manufacturing or production based on the technical content disclosed in this application are just conventional technical means, and should not be understood as the content disclosed in this application is insufficient.

[0035] However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially the same structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.

[0036] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution, and all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0037] The first aspect of the embodiment of the present application provides a method for quantitatively detecting the crystallization rate of mold slag, comprising the following steps:

[0038] S1. After the mold slag is melted, kept warm and cooled, image analysis is performed to obtain the crystallization rate of the mold slag;

[0039] The insulation temperature is 1300°C to 1400°C, and the insulation time is more than 30 minutes.

[0040] The embodiment of the present application provides a quantitative detection method for the crystallization rate of mold slag. After the mold slag is melted, it is kept warm for a certain period of time so that the components in the slag are evenly mixed. The quantitative detection method has simple steps and is easy to operate. Before the mold slag is put into use, the crystallization rate of the mold slag is quantitatively detected under the same conditions, and then the crystallization ability of different mold slags is compared, providing a theoretical basis and guidance for the application and composition optimization of continuous casting mold slag.

[0041] The embodiment of the present application provides a method for quantitatively detecting the crystallization rate of the protective slag, so the component composition of the protective slag is determined by the crystallization rate of the protective slag that actually needs to be detected, and does not need to be specifically limited in the embodiment of the present application. However, as an example, the protective slag can be composed of the following components by mass fraction:

[0042] ① The first component: 13.29% C, 31.68% CaO, 29.73% SiO2, 3.56% Al2O3, 10.90% (Na2O+K2O), 4.40% MgO, 0.68% Fe2O3, 5.76% F, basicity is 1.07.

[0043] ②The second component: 9.37% C, 38.41% CaO, 27.96% SiO2, 4.09% Al2O3, 8.83% (Na2O+K2O), 0.99% MgO, 0.72% Fe2O3, 9.63% F, basicity is 1.37.

[0044] ③The third component: 5.65% C, 44.21% CaO, 27.71% SiO2, 2.82% Al2O3, 7.75% (Na2O+K2O), 2.13% MgO, 9.73% F, basicity is 1.6.

[0045] In some embodiments, in the above step S1, the basicity of the mold slag is 0.5-2.0, and in the exemplary example, it can be a typical but non-limiting basicity such as 1.07, 1.37, 1.60, or a range between any two basicities. In this case, the mold slag is a medium-high basicity mold slag, and the cooling rate, the quality of the mold slag and other conditions have a large difference in its crystallization performance, and the conventional sampling method for detecting the crystallization rate cannot accurately detect its crystallization rate.

[0046] Basicity refers to the mass ratio of basic oxides to acidic oxides in the protective slag, such as m(CaO) / m(SiO2).

[0047] In some embodiments, in the above step S1, the protective slag is a carbon-free protective slag. In this case, when the carbon-free protective slag is used in steel smelting and continuous casting, it has the functions of preventing carbon increase of molten steel, heat insulation, reducing heat loss, absorbing and dissolving non-metallic inclusions, etc., thereby optimizing the continuous casting process.

[0048] In some embodiments, the weight fraction of the carbon-free protective slag is 200 to 300 parts. In exemplary embodiments, it can be 200 parts, 250 parts, 300 parts, or other typical but non-limiting weight fractions or a range between any two weight fractions.

[0049] In some specific embodiments, the weight percentage of the carbon-free protective slag is 250 parts to 260 parts.

[0050] In some embodiments, in the above step S1, the melting step includes: heating the mold slag to 1300°C to 1400°C at a heating rate of 10°C / min to 15°C / min.

[0051] In some specific embodiments, the melting step includes: placing the protective slag in a graphite crucible, and heating the protective slag to 1300°C to 1400°C in a high-temperature silicon-molybdenum furnace at a heating rate of 10°C / min to 15°C / min. In this case, the graphite crucible has excellent chemical stability and can resist corrosion from a variety of chemical substances. In the process of melting the protective slag, the graphite crucible can effectively prevent the molten material from chemically reacting with the crucible wall, thereby avoiding contamination of the protective slag components and ensuring the purity of the smelting; in the high-temperature silicon-molybdenum furnace, the protective slag is evenly melted, and after being kept warm for a certain period of time, a stable and uniform liquid slag can be formed, thereby effectively playing its due function. In addition, the high-temperature silicon-molybdenum furnace has high heating efficiency, can quickly and stably reach the melting temperature, reduce the melting time, and improve production efficiency.

[0052] In some embodiments, in the above step S1, the insulation time is 30 min to 60 min. In the exemplary embodiment, it can be a typical but non-limiting time such as 30 min, 40 min, 50 min, 60 min, or a range between any two times.

[0053] In some embodiments, in the above step S1, the crystallization step includes: cooling the mold slag after heat preservation to 23°C to 28°C at a cooling rate of 20°C / s to 50°C / s to obtain a crystallized sample. In this case, the mold slag is rapidly cooled and solidified, and the crystallization rate of the mold slag after cooling can be observed, thereby evaluating the lubrication and heat transfer control capabilities of the mold slag during the continuous casting process.

[0054] In some embodiments, the cooling method of the mold slag includes air cooling or wind cooling.

[0055] In some specific embodiments, the crystallization step includes: pouring the melted and heat-insulated protective slag into a stainless steel container, cooling it to 23°C to 28°C by air cooling at a cooling rate of 20°C / s to 50°C / s, and obtaining a crystallized sample. In this case, the stainless steel container has excellent corrosion resistance and can resist the erosion of various chemical substances. In the process of crystallizing the protective slag, the stainless steel container can effectively prevent the molten material from chemically reacting with the container wall, thereby avoiding contamination of the protective slag components and ensuring the purity and stability of the protective slag.

[0056] In some specific embodiments, the time for pouring the melted and heat-insulated protective slag into the stainless steel container is 2s to 5s.

[0057] In some specific embodiments, the thickness of the crystal sample is 0.8 cm to 1.2 cm. In the exemplary embodiment, it can be a typical but non-limiting thickness such as 0.8 cm, 1.0 cm, 1.2 cm, or a range between any two thicknesses. In this case, a sample with a thickness of about 1 cm can be achieved, and the crystallization rate of the slag can be observed from its cross section. It should be noted that the size of the stainless steel container is not particularly limited in the embodiments of the present application, as long as the thickness of the crystal sample can be 0.8 cm to 1.2 cm, but as an example, the size of the stainless steel container can be: inner diameter 100 mm, height 80 mm, wall thickness 15 mm, bottom thickness 25 mm.

[0058] In some embodiments, in the above step S1, the image analysis step includes:

[0059] S11. Obtaining analysis samples;

[0060] S12. Obtain a longitudinal cross-sectional photograph of the analysis sample;

[0061] S13. Use image analysis software to identify and obtain the crystallization rate of the analyzed sample.

[0062] In the above-mentioned image analysis step, the analysis sample is analyzed (automatically) identified using image software, and the crystallization rate of the longitudinal section of the cooled sample is determined based on the color and pixel differences of the image.

[0063] In some specific embodiments, in the above step S11, the step of obtaining the analysis sample includes:

[0064] According to the size of the analysis sample, the analysis sample is obtained by longitudinally cutting from the crystal surface of the crystal sample to the other side away from the crystal surface.

[0065] The above steps of obtaining the analytical sample, the analytical sample obtained completely includes the crystal surface of the crystal sample and the other side away from the crystal surface, which is conducive to analyzing the crystallization rate of the crystal sample.

[0066] The crystalline surface refers to a surface containing a crystalline portion and having the largest crystalline area.

[0067] In other specific embodiments, in the above step S11, the step of obtaining the analysis sample includes: according to the size of the analysis sample, longitudinally cutting from the top (upper surface) of the crystal sample to the bottom (lower surface) of the crystal sample to obtain the analysis sample.

[0068] The bottom (lower surface) refers to the crystal-like surface portion in contact with the bottom of the stainless steel container in the container.

[0069] The top (upper surface) refers to the portion of the surface of the crystal-like in the container that is parallel to and faces away from the bottom (lower surface).

[0070] In some specific embodiments, in the above step S11, the size (length×width×thickness) of the analyzed sample is (10-100) mm×(8-12) mm×(10-100) mm, except for 10 mm×(8-12) mm×10 mm. From another perspective, if the size is smaller than this, the fracture morphology of the longitudinal section slag sample cannot be fully observed.

[0071] In some specific embodiments, in the above step S12, the step of obtaining a longitudinal cross-section photograph of the analysis sample includes:

[0072] A camera is used to capture the longitudinal section of the analyzed sample.

[0073] In some specific embodiments, the resolution of the camera is 20 million pixels or more. In this case, the high resolution of the camera obtains a high-definition photo of the longitudinal section, thereby being able to capture more details and making the fracture morphology clearer.

[0074] In some specific embodiments, in the above step S12, the number of photos is at least 1, can be 1 to 3, and preferably 1.

[0075] In some specific embodiments, in the above step S13, the image analysis software is Adobe Photoshop or Image J. In this case, the crystallization rate of the longitudinal section of the cooled sample is automatically generated and determined based on the color and pixel differences of the image displayed by the image analysis software.

[0076] In some specific embodiments, when Adobe Photoshop is used to analyze sample photos, the RGB values ​​of the crystallized part in the photos are: R value is 60-190, G value is 50-200, and B value is 45-195.

[0077] In some specific embodiments, when ImageJ is used to analyze sample photos, the RGB values ​​of the crystalline part in the photos are: R value is 60-190, G value is 50-200, and B value is 45-195.

[0078] In some specific embodiments, when the crystalline phase in the original image of the photo is processed using Adobe Photoshop or ImageJ, the image needs to be imported into Adobe Photoshop or ImageJ software. The software marks the crystalline phase part as red according to the pixels, while the non-crystalline part is still marked as the original color. Finally, the area ratio of the red area is calculated as the crystallization rate.

[0079] In some specific embodiments, a method for quantitatively detecting the crystallization rate of mold slag is provided, comprising the following steps:

[0080] S20. Obtain protective slag to be tested.

[0081] S21. The protective slag is placed in a graphite crucible, and the temperature is raised to 1300°C to 1400°C in a high-temperature silicon-molybdenum furnace at a heating rate of 10°C / min to 15°C / min, and then kept warm for more than 30 minutes.

[0082] S22. Pour the melted and heat-insulated protective slag into a stainless steel container within 2s to 5s, and air-cool it to 23°C to 28°C at a cooling rate of 20°C / s to 50°C / s to obtain a crystalline sample.

[0083] S23. According to the size of the analysis sample, cut longitudinally from the crystal surface of the crystalline sample to the other side away from the crystal surface to obtain the analysis sample. The size of the analysis sample is (10~100)mm×(8~12)mm×(10~100)mm, except for 10mm×(8~12)mm×10mm.

[0084] S24. Use a camera with a resolution greater than 20 million pixels to take at least one longitudinal cross-section of the analyzed sample.

[0085] S25. Use ImageJ or Adobe Photoshop image analysis software to analyze and obtain the crystallization rate of the analyzed sample.

[0086] A second aspect of an embodiment of the present application provides an application of the method for quantitatively detecting the crystallization rate of protective slag provided in an embodiment of the present application in the field of steel smelting technology.

[0087] The following is further described in conjunction with specific embodiments.

[0088] Example 1

[0089] Embodiment 1 provides a method for quantitatively detecting the crystallization rate of mold slag, and the steps are as follows:

[0090] (1) Obtain 250 g of the mold slag to be tested, which is composed of the following components by mass fraction:

[0091] 13.29% C, 31.68% CaO, 29.73% SiO2, 3.56% Al2O3, 10.90% (Na2O+K2O), 4.40% MgO, 0.68% Fe2O3, 5.76% F. The basicity of the mold slag is 1.07.

[0092] (2) The mold slag is heated to 1300°C at a heating rate of 15°C / min and kept at 1300°C for 30 min.

[0093] (3) Cooling to 25°C by air cooling at a cooling rate of 30°C / s to obtain a crystal sample with a thickness of 10 mm.

[0094] (4) An analytical sample was cut from the crystal sample, and the size of the analytical sample was 12 mm × 10 mm × 12 mm.

[0095] (5) Use a camera with a resolution of 20 million pixels to take a longitudinal cross-section of the analyzed sample.

[0096] (6) ImageJ image analysis software was used to analyze the crystallization rate of the analyzed samples.

[0097] Example 2

[0098] Example 2 proposes a method for quantitatively detecting the crystallization rate of mold slag, and the steps are basically the same as those of Example 1, except that:

[0099] The protective slag in step (1) is composed of the following components in mass fractions:

[0100] 9.37% C, 38.41% CaO, 27.96% SiO2, 4.09% Al2O3, 8.83% (Na2O+K2O), 0.99% MgO, 0.72% Fe2O3, 9.63% F. The basicity of the mold slag is 1.37.

[0101] Example 3

[0102] Example 3 proposes a method for quantitatively detecting the crystallization rate of mold slag, and the steps are basically the same as those of Example 1, except that:

[0103] The protective slag in step (1) is composed of the following components by mass fraction: 5.65% C, 44.21% CaO, 27.71% SiO2, 2.82% Al2O3, 7.75% (Na2O+K2O), 2.13% MgO, and 9.73% F. The basicity of the protective slag is 1.6.

[0104] Example 4

[0105] Example 4 proposes a method for quantitatively detecting the crystallization rate of mold slag, and the steps are basically the same as those of Example 2, except that:

[0106] Step (2) The protective slag is heated to 1350°C at a heating rate of 10°C / min and kept at this temperature for 40 minutes.

[0107] The cooling rate in step (3) is 20°C / s.

[0108] Example 5

[0109] Example 5 proposes a method for quantitatively detecting the crystallization rate of mold slag, and the steps are basically the same as those of Example 2, except that:

[0110] Step (2) The protective slag is heated to 1400°C at a heating rate of 15°C / min and kept at this temperature for 50 minutes.

[0111] The cooling rate in step (3) is 50°C / s.

[0112] Comparative Example 1

[0113] Comparative Example 1 proposes a method for quantitatively detecting the crystallization rate of mold slag, and the steps are basically the same as those of Example 2, except that:

[0114] The melted protective slag in step (2) is not kept warm.

[0115] The thickness of the crystal sample in step (3) is 5 mm.

[0116] Comparative Example 2

[0117] Comparative Example 2 proposes a method for quantitatively detecting the crystallization rate of mold slag, and the steps are basically the same as those of Example 2, except that:

[0118] The insulation temperature of the protective slag in step (2) is 1450° C. and the insulation time is 20 min.

[0119] The cooling rate in step (3) is 60°C / s.

[0120] Comparative Example 3

[0121] Comparative Example 3 proposes a method for analyzing the crystallization rate of mold protection slag film, and the steps are as follows:

[0122] Step 1 Sampling: The protective slag is directly applied to the continuous casting step of steel smelting. After smelting once, the solid slag film located in the middle position below the meniscus of the crystallizer wall is taken out from the steel smelting site; the selected protective slag is composed of the following components by mass fraction: 9.37% C, 38.41% CaO, 27.96% SiO2, 4.09% Al2O3, 8.83% (Na2O+K2O), 0.99% MgO, 0.72% Fe2O3, 9.63% F. The basicity of the protective slag is 1.37.

[0123] Step 2: Mounting: Fix the sample into the mold and add resin for mounting.

[0124] Step 3: Grinding and polishing: Grind and polish the mounted sample until no obvious scratches are visible under an optical microscope.

[0125] Step 4: Image analysis: Crystallization performance analysis is performed by image method.

[0126] In order to verify the progress of the quantitative detection method of the crystallization rate of the protective slag provided in the examples of the present application, the crystallization rate results of the analysis samples obtained in the examples and comparative examples are shown in Table 1 below. Figures 1 to 5Furthermore, taking Example 2 as an example, the method of using ImageJ image analysis software to analyze the crystallization rate of the analyzed sample is as follows:

[0127] Will be like Figure 2 The picture shown is imported into ImageJ software, and the software marks the crystalline phase part as red according to the pixels (RGB values: R value is 60-190, G value is 50-200, B value is 45-195), while the non-crystalline part is still marked as the original color, such as Figure 6 As shown; finally, the area ratio of the red region is calculated as the crystallization rate, and the crystallization rate of Example 2 is 53.1%.

[0128] Table 1

[0129] - Crystallinity (%) Example 1 0.0 Example 2 53.1 Example 3 100.0 Example 4 58.3 Example 5 31.9 Comparative Example 1 0.0 Comparative Example 2 0.0 Comparative Example 3 40.52

[0130] According to Table 1 above and the instructions attached Figures 1 to 5 At least the following conclusions can be drawn:

[0131] (1) By Figures 1 to 5 , combined with the data in Table 1, it can be seen that the crystallization of Example 1 is in a glassy state, Example 2 is 50% crystal, and Example 3 is 100% crystal. Compared with Example 2, when the mass of the protective slag in Comparative Example 1 is 100g and the thickness of the crystal sample is 5mm, since the fracture morphology of the slag is glassy (under the same cooling conditions, the less the amount of slag, the greater the degree of supercooling of the slag per unit area, that is, the greater the cooling rate, the easier it is to generate glass), it is impossible to accurately reflect the crystallization rate of the protective slag. Compared with Example 2, in Comparative Example 2, the insulation temperature is controlled at 1450°C, and the fracture morphology of the poured slag is glass, which also cannot accurately reflect the crystallization of the protective slag. It can be seen that the mass of the protective slag and the pouring temperature (that is, the insulation temperature) will affect the fracture crystallization rate of the crystal sample; and then the weight and temperature range of the protective slag specified in the quantitative detection method of the crystallization rate of the protective slag in the embodiment of the present application can be adopted, so that the crystallization rate of the protective slag can be quantitatively detected at the same weight range and temperature level.

[0132] (2) The method for quantitatively detecting the crystallization rate of the protective slag in the embodiment of the present application is simple in steps and easy to operate. The crystallization rate of the protective slag is quantitatively detected before the protective slag is put into use, and then the crystallization ability of different protective slags is compared, thereby providing a basis and guidance for the application and composition optimization of the continuous casting protective slag.

[0133] (3) It can be seen from Example 2 and Comparative Example 3 in Table 1 that the crystallization rate of the protective slag detected by on-site sampling is lower than the crystallization rate of the protective slag detected by the quantitative detection method of the protective slag crystallization rate of the embodiment of the present application, which indicates that the crystallization rate of the protective slag is affected by the current conditions of steel continuous casting (such as composition, temperature, etc.), and the detected crystallization rate cannot reflect the crystallization strength of the protective slag itself. Therefore, the quantitative detection method of the crystallization rate of the protective slag of the embodiment of the present application is detected under conditions not affected by any external factors, and the crystallization rate obtained is the crystallization strength of the protective slag itself, which provides a theoretical basis for the use of the protective slag.

[0134] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for quantitatively detecting the crystallization rate of mold slag, characterized in that: The steps include: After the mold slag is melted, kept warm and cooled, image analysis is performed to obtain the crystallization rate of the mold slag; The insulation temperature is 1300° C. to 1400° C., and the insulation time is more than 30 minutes.

2. The method for quantitatively detecting the crystallization rate of mold slag according to claim 1, characterized in that: The basicity of the protective slag is 0.5-2.

0.

3. The method for quantitatively detecting the crystallization rate of mold slag according to claim 1 or 2, characterized in that: The protective slag is carbon-free protective slag.

4. The method for quantitatively detecting the crystallization rate of mold slag according to claim 1, characterized in that: The insulation time is 30 minutes to 60 minutes.

5. The method for quantitatively detecting the crystallization rate of mold slag according to any one of claims 1 to 4, characterized in that: The cooling step comprises: cooling the mold slag after heat preservation to 23°C to 28°C at a cooling rate of 20°C / s to 50°C / s to obtain a crystal sample.

6. The method for quantitatively detecting the crystallization rate of mold slag according to claim 5, characterized in that: The image analysis step comprises: Obtaining samples for analysis; Obtaining a longitudinal cross-sectional photograph of the analysis sample; The crystallization rate of the analyzed sample is identified and obtained using image analysis software.

7. The method for quantitatively detecting the crystallization rate of mold slag according to claim 6, characterized in that: The size of the analysis sample is 10 mm to 100 mm × 8 mm to 12 mm × 10 mm to 100 mm, except for 10 mm × 8 mm to 12 mm × 10 mm.

8. The method for quantitatively detecting the crystallization rate of mold slag according to claim 6, characterized in that: The image analysis software is Adobe Photoshop or ImageJ.

9. The method for quantitatively detecting the crystallization rate of mold slag according to claim 8, characterized in that: When the Adobe Photoshop or the ImageJ is used to analyze the sample photo, the RGB values ​​of the crystal part in the photo are: R value is 60-190, G value is 50-200, and B value is 45-195.

10. Application of the method for quantitatively detecting the crystallization rate of mold slag as claimed in any one of claims 1 to 9 in the field of steel smelting technology.